(untitled) (Research, Society and Development, 2021)
Drug addiction is considered a worldwide public health problem. There are few effective pharmacotherapeutic options for this condition treatment. However, the use of serotonergic hallucinogenic molecules from plants used in religious contexts such as those found in Mimosa tenuiflora root bark and Anadenanthera colubrina seeds have great therapeutic potential by reducing addictive behaviors associated with abstinence. This paper presents the ethnopharmacological, phytochemical, pharmacological, and toxicological characteristics that can support the plants study Mimosa tenuiflora and Anadenanthera colubrina in drug addiction treatment. During this in narrative review, 159 texts were evaluated where it was possible to observe that there are justifications that can endorse the therapeutic investigation of these of these plants, especially when verifying the presence of serotoninergic hallucinogenic molecules such as N, N-dimetiltriptamine and 5-OH-N, N-dimetiltriptamine opening, therefore, the possibility of developing and producing new anti-addict therapeutic options.